Coronary artery spasm: Current knowledge and residual uncertainties. (March 2016) - Slavich, Massimo; Patel, Riyaz Suleman
Abstract: Myocardial ischaemia results from a direct mismatch between oxygen supply and demand, commonly arising as a result of coronary atherosclerosis, microvascular dysfunction or acute thrombosis and luminal obstruction. However, transient ischaemia may also occur due to coronary spasm leading to acute and unexpected myocardial ischaemia without obvious visible coronary pathology. Aside from symptoms of chest pain, coronary spasm can cause infarction, LV impairment, promote life threatening arrhythmias and ultimately sudden cardiac death. While therapeutic options are available, controversies exist around diagnosis, pathology, management and prognosis. This review summarises some of the common questions in this area. In particular we explore and discuss the available evidence for the pharmacological treatment of coronary spasm, and strategies for identification and management of very high risk patients to try and reduce the incidence of sudden premature death. Highlights: Myocardial ischaemia results from a mismatch between oxygen supply and demand. Spasm might lead to myocardial ischaemia without visible coronary pathology. Coronary spasm can cause infarction, LV impairment and sudden cardiac death.